The Effect Of Combining Oxytocin Massage And Breast Care On Breast Milk Adequacy In Postpartum Mothers In The Working Area Of Poncowati Health Center, Central Lampung Regency, 2024 - Diana, Diana; Beniqna Maharani Besmaya; Nur Alfi Fauziah; Hikmah Ifayanti (Jurnal EduHealth, 2024)
According to WHO in 2021, only 42% of countries provided exclusive breastfeeding from the target of 75%. In Lampung Province, there was a decrease in coverage of infants less than 6 months receiving exclusive breastfeeding from 76.76% in 2022 to 76.20%. Breastfeeding failure is often caused by several problems, one of which is insufficient milk production. Non-pharmacological methods to increase milk production are oxytocin massage and breast care. Oxytocin massage functions to stimulate the oxytocin reflex, calming the mother, so that breast milk flows naturally, while breast care is an action to care for the breasts, especially to facilitate breastfeeding. The research aim was to determine the effect of combining oxytocin massage and breast care on breast milk adequacy in postpartum mothers. The research method was pre-experimental using a one-group pre-posttest design approach by providing oxytocin massage intervention. It was given to postpartum mothers on days 5-9 twice daily, morning and evening. The population in this study was 42 breastfeeding postpartum mothers. The sampling technique used purposive sampling with a sample size of 20 postpartum mothers. Indicators of breast milk adequacy were seen from urination frequency, feeding frequency, and changes in baby's weight. This research was conducted in the Poncowati Health Center Area, Central Lampung Regency in 2024. Data analysis used the Wilcoxon test (for urination and feeding frequency) and Paired Sample Test (for baby's weight changes). Research results showed the average baby feeding frequency before was 7 times and after was 10 times, baby urination frequency before was 6 times and after was 8 times, baby weight before was 3094 grams and after was 3301.5 grams. The conclusion with p-values for feeding 0.000 (<0.05), baby urination 0.000 (<0.05), and baby weight 0.000 (<0.05) means there is an effect of combining oxytocin massage and breast care on breast milk adequacy in postpartum mothers. The research suggests that postpartum mothers can perform a combination of oxytocin massage and breast care as therapy to increase milk production.